Improving the quality and extending the shelf-life of fresh-cut mushrooms - Gonçalves, Francisco José Fonseca (2020)
Fresh-sliced mushrooms have a fast quality degradation and a relative short shelf-life, maximum 6 days. In the present work was studied the possibility of application of modified atmosphere packaging to extend the shelf-life and to improve the quality of fresh-sliced mushrooms Agaricus bisporus. The tests were done in Holland, at Royal Vezet BV, one of the biggest European freshcut processors. It was selected the variant Sliced mushroom’s packed in bags of 200g to be tested in this study. Samples from fresh-sliced mushrooms were collected from Royal Vezet production lines and his respiration rate was measured. A number of variations to the standard Royal Vezet process parameters were tested. Samples from sliced mushrooms were produced and the respiration rate (RR) was measured. The results from the measurement of the respiration rate were used to calculate de ideal modified atmosphere packaging (MAP). To measure the mushrooms RR an innovative technology was used, the Respiration Meter from PerfoTec BV. This new technology can, simultaneously, measure the oxygen (O2) consumption and carbon dioxide (CO2) release, resulting from the product respiratory activity. Shelf-life tests from the tested product were done to check the effectiveness of the results. The mushrooms evidenced to have a high RR. At the optimal processing temperatures, the main factor tested able to slowdown the RR was the increase of cutting size of the mushroom’s slices. Lowering the initial package oxygen percentage did not improve the shelf life. According with this work the MAP specifications for fresh-sliced mushrooms (5mm) packed in bags of 200 g are: Film material - OPP, bag size - 170 mm height and 400 mm width, Perforations- 8 perforations per bag with 90 µm hole size and spaced by 38 mm. The new packaging improved the product quality but did not improve its shelf-life.